M9 Psychosocial impact of mycobacterium abscessus infection in adults with cystic fibrosis. (12th November 2019) - Zaki, SFH; Chapman, KSA; Chapman, SJ; Flight, WG
Abstract : Background: People with cystic fibrosis (CF) are at increased risk of psychological morbidity but any additional impact of infection with transmissible pathogens such as Mycobacterium abscessus on psychological status is unclear. We hypothesised that M. abscessus infection may lead to an additional psychological burden, perhaps as a result of complex treatment regimens or enhanced measures to prevent cross-infection. Methods: Patients with CF and a history of M. abscessus infection attending our centre were identified. The Hospital Anxiety and Depression Scale (HADS) and the CF Quality of Life (CFQoL) scores at annual review before and after diagnosis of M. abscessus infection were compared. Controls with CF but no history of M. abscessus infection were identified and matched for age, sex and lung transplant status. Most recent HADS and CFQoL scores in the two groups were compared, with better psychological wellbeing represented by lower HADS and higher CFQoL scores. Results: Twenty-five patients with a history of M. abscessus infection and 25 controls were included. The groups were well matched with mean age 30.0 (SD=11.0) in the M. abscessus group and 29.6 years (SD=9.7) among controls. Male:female ratio was 15:10 in both groups. Mean FEV1%-predicted was 60.1% (SD=21.9) in the M. abscessus group and 69.1% (SD=23.1) among controls. Mean body mass index was 21.6 kg/m 2 (SD=5.3) and 21.5 kg/m 2 (SD=3.8) respectively. Mean HADS score in the M. abscessus group was 13.0 (SE=3.0) compared to 7.8 (SE=1.7) for controls. The mean CFQoL score was 68.8 (SE=5.1) in the M. abscessus group compared with 71.5 (SE=4.6) for controls. When including all recorded questionnaire scores, there was an inverse correlation between HADS and CFQoL scores (R 2 =0.657, n=110) with individual patient R 2 values ranging from 0.0006 to 0.8751. 7/25 (28%) patients had complete HADS and CFQoL data before and after M. abscessus infection. Mean HADS was 7.7 (SE=2.4) before and 8.1 (SE=2.8) after M. abscessus infection while the mean CFQoL increased from 71 (SE=7.8) to 79 (SE=6.5). Conclusions: Mycobacterium abscessus infection in adults with CF may be associated with lower psychological wellbeing. Larger studies are required to confirm this association and explore possible causes.